The Impact of Administrative Empowerment on Enhancing Organizational Affiliation: A Field Study on the Administrative Staff of the Education Department in Al-Leith Governorate - Almalki, Abdullah Hamed A.; Shuaibi, Faisal Ahmed (The Arab Journal of Administration, 2024)
The study aimed to identify the effect of administrative empowerment in enhancing the organizational affiliation of the administrative staff of the Education Department in Al-Leith Governorate, by measuring the dimensions of administrative empowerment represented in (delegating authority, sharing information, work teams, training, motivation) on enhancing organizational affiliation, and the study used a Descriptive and analytical approach, and it adopted the questionnaire as a main tool for collecting study data from a random sample of (152) administrative employees in the Education Department in Al-Leith Governorate. Descriptive and analytical statistical tests were performed to test the study hypotheses, using the statistical package for social sciences SPSS. The study results include: the presence of high level organizational affiliation among the employees of the education department in Al-Laith Governorate from the respondents’ point of view, and therefore it can be noted that the organizational affiliation of employees can be enhanced through the application of administrative empowerment of employees and giving them more powers to continue giving within their organizations. The study also revealed a statistically significant effect between administrative empowerment in its various dimensions on enhancing organizational affiliation at the significance level of 0.05 The study recommends a number of recommendations, the most important of which are: Defining the importance of administrative empowerment and granting greater powers to employees and linking them to the goals and programs of the Saudi’s Vision 2030, as well as continuously updating the dimensions of administrative empowerment according to the requirements of each stage to achieve the desired results of the administrative empowerment process, strengthening the positive aspects and addressing the negative aspects, in addition to the necessity of Focusing efforts to activate the role of administrative empowerment in its various dimensions in accordance with the Saudi’s vision 2030 to take advantage of the current and future capabilities of the administrative employee to continue achieving excellence and success in government departments.